Individual and cumulative effects of social determinants of health on cardiovascular disease: Gender-specific insights from a cross-sectional NHANES study - Xiuming Yang; Jiahui Zhou; Feier Wu; Zehu Xue; Zongliang Yu (PLoS ONE, 2026)
Objective This study aimed to examine the associations of individual and cumulative social determinants of health (SDoH) with cardiovascular disease (CVD) prevalence and sex-specific disparities among U.S. adults. Methods Employing a cross-sectional design, we analyzed data from the nationally representative National Health and Nutrition Examination Survey (NHANES, 2005–2018). Five core SDoH domains were operationalized through eight validated sub-indicators. Associations between individual and cumulative SDoH and CVD prevalence were assessed using survey-weighted multivariate logistic regression, with sex-stratified analyses. Results In this cross-sectional sample of 35,781 participants, adverse individual SDoH and higher cumulative adverse SDoH were associated with higher odds of prevalent CVD. In the fully adjusted model (Model 2), unemployment showed a large association with prevalent CVD (AOR = 2.27, 95% CI: 2.01–2.57). In sex-stratified analyses, point estimates for some SDoH indicators were higher in women than in men, but 95% confidence intervals overlapped for many comparisons and sex-by-SDoH interaction tests were not statistically significant (all P for interaction > 0.05). Among individual SDoH indicators, unemployment and low income (PIR < 300%), as well as food insecurity, showed the strongest independent associations with prevalent CVD. Conclusion Both individual and cumulative SDoH were independently associated with prevalent CVD. Sex-stratified analyses suggested that some point estimates were larger in women than in men, but sex-by-SDoH interaction tests were not statistically significant.